Kontribusi Karakteristik Pasien Gagal Ginjak Kronik dengan Hemodialisis pada Pengetahuan dan Kepatuhan Pengobatan - Agustina Nila Yuliawati; Pande Made Desy Ratnasari; Ni Ketut Kristina Dewi; I Gusti Ayu Putu Priyanti (Jurnal Farmasi Indonesia, 2023)
The knowledge and adherence of end-stage renal disease (ESRD) patients can vary based on their characteristics, then could influence the success of their therapy. This study aimed to determine the contribution of ERSD patients’ characteristics undergoing hemodialysis (HD) to their knowledge and adherence. Data were collected using questionnaires including the CKD-KQ, the ESRD-AQ, and respondent identity sheets sourced from medical records. The relationship between respondent characteristics and their knowledge and adherence was analyzed using bivariate statistical tests. Findings showed that the average respondent had a knowledge score of 18.12±3.40 (max.24) and adherence of 1092.86±135.20 (max.1200). Patient characteristics contribution in adherence was found in the age and suffering from ESRD undergoing HD duration (p<0.05), but not with patient knowledge. Other elements such as providing education from health workers are considered to increase patient knowledge, and the ease of undergoing ESRD therapy has an impact on high patient adherence(p<0.05).